Стендові гідравлічні випробування макету бурильних труб - Гошовський, С.В.; Кожевников, А.О.; Кузін, Ю.Л.; Лексиков, О.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
In clause results of bench researches of losses of a pressure in boring pipes wich various internal diameter are resulted at various charges drilling fluid liquids.